Direction of Arrival Estimation of GNSS Signal using Dual Antenna - Ong, Junho; So, Hyoungmin (Journal of Positioning, Navigation, and Timing, 2020)
This paper deal with estimating the direction of arrival (DOA) of GNSS signal using two antennae for spoofing detection. A technique for estimating the azimuth angle of a received signal by applying the interferometer method to the GPS carrier signal is proposed. The experiment assumes two antennas placed on the earth's surface and estimates the azimuth angle when only GPS signal are received without spoofing signal. The proposed method confirmed the availability through GPS satellite placement simulation and experiments using a dual antenna GPS receiver. In this case of using dual antenna, an azimuth angle ambiguity of the received signal occurs with respect to the baseline between two antennas. For this reason, the accurate azimuth angle estimation is limits, but it can be used for deception by cross-validating the ambiguity.